UMP lecturers encouraged to share expertise through writing - Mohd Halimi, Abdul Aziz (2021)
KUANTAN, 29 July 2021 - Universiti Malaysia Pahang (UMP) lecturers are encouraged to share ideas, thoughts, suggestions and views based on their knowledge expertise through writings published in newspapers, magazines or popular portals.